Reduction in Post-Marathon Peak Oxygen Consumption: Sign of Cardiac Fatigue in Amateur Runners? - Sierra,Ana Paula Rennó (2016)
Abstract Background: Prolonged aerobic exercise, such as running a marathon, produces supraphysiological stress that can affect the athlete's homeostasis. Some degree of transient myocardial dysfunction ("cardiac fatigue") can be observed for several days after the race. Objective: To verify if there are changes in the cardiopulmonary capacity, and cardiac inotropy and lusitropy in amateur marathoners after running a marathon. Methods: The sample comprised 6 male amateur runners. All of them underwent cardiopulmonary exercise testing (CPET) one week before the São Paulo Marathon, and 3 to 4 days after that race. They underwent echocardiography 24 hours prior to and immediately after the marathon. All subjects were instructed not to exercise, to maintain their regular diet, ingest the same usual amount of liquids, and rest at least 8 hours a day in the period preceding the CPET. Results: The athletes completed the marathon in 221.5 (207; 250) minutes. In the post-marathon CPET, there was a significant reduction in peak oxygen consumption and peak oxygen pulse compared to the results obtained before the race (50.75 and 46.35 mL.kg-1 .min-1; 19.4 and 18.1 mL.btm, respectively). The echocardiography showed a significant reduction in the s' wave (inotropic marker), but no significant change in the E/e' ratio (lusitropic marker). Conclusions: In amateur runners, the marathon seems to promote changes in the cardiopulmonary capacity identified within 4 days after the race, with a reduction in the cardiac contractility. Such changes suggest that some degree of "cardiac fatigue" can occur.